THE INFLUENCE OF REMUNERATION, LEADERSHIP, ORGANIZATIONAL CULTURE, INTERNAL CONTROL, AND MANAGEMENT INFORMATION SYSTEMS ON IMPROVING PERFORMANCE THROUGH JOB SATISFACTION AS INTERVENING VARIABLES AT THE BATAM CUSTOMS AND EXCISE MAIN SERVICE OFFICE - Munandar; Angelina E. Rumengan; Muammar Khaddafi; Chablullah Wibisono; Indrayani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to determine the influence of Remuneration, Leadership, Organizational Culture, Internal Control, and Management Information Systems on Performance Improvement through Job Satisfaction as an Intervening Variable at the Batam Customs and Excise Main Service Office. In this paper, the research design used is a descriptive method with a quantitative approach. The population of this research is all ASN employees at the Batam Customs and Excise Main Service Office. Based on data obtained by the author, the number of employees with ASN status was 562 people, with details of 490 men and 72 women, so the total sample in this study was 234 people. The questionnaire was distributed via the Google Form link with an estimated data collection period of one month. , after the data is collected it is then processed and analyzed further using smartPLS 3.0 SEM (Partial Least Square-Structural Equation Modeling) software. Based on the results of hypothesis testing on all independent variables, it shows that Remuneration, Leadership, Organizational Culture and Internal Control have no significant effect on job satisfaction, while management information systems have a significant effect on job satisfaction. Furthermore, job satisfaction and organizational culture have a significant effect on performance. Meanwhile, remuneration, leadership, internal control and management information systems have no significant effect on performance. Then Remuneration, Leadership, Organizational Culture, and Internal Control have no significant effect on performance through job satisfaction, while management information systems have a significant effect on performance through job satisfaction. The magnitude of the influence of remuneration, leadership, organizational culture, internal control and management information systems on job satisfaction is 0.7398 or around 73.98%. Meanwhile, remuneration, leadership, organizational culture, internal control and management information systems on performance were 0.7698 or 76.98%. Meanwhile, the rest is influenced by other variables outside this research model